Pengaruh Kinerja Lingkungan dan Penerapan Akuntansi Manajemen Lingkungan terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2024 - Meida Widianingrum; Sairun Simanullang; Ida Harahap (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the effect of environmental performance and the application of environmental management accounting on financial performance in food & beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2024. The study uses quantitative data, sourced from secondary data such as annual reports, the Ministry of Environment and Forestry website, and company websites. A purposive sampling method was applied to select 14 companies for a 6-year observation period, resulting in 79 data points after the outlier process. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing via SPSS version 25. The results indicate that both environmental performance and environmental management accounting affect financial performance. The simultaneous F test showed a significance value of 0.023 < 0.05, meaning both variables influence the dependent variable. The first partial hypothesis test revealed that environmental performance (X1) significantly affects financial performance (Y) with a significance value of 0.006 < 0.05. In contrast, the second partial hypothesis test found that the application of environmental management accounting (X2) does not affect financial performance (Y) with a significance value of 0.771 > 0.05. The coefficient of determination was 0.390, suggesting that 39% of the financial performance is explained by the two independent variables, while the remaining 61% is influenced by other factors.